2014
DOI: 10.1128/jb.01981-14
|View full text |Cite
|
Sign up to set email alerts
|

Spermidine Biosynthesis and Transport Modulate Pneumococcal Autolysis

Abstract: Polyamines are small cationic molecules that have far-reaching roles in biology. In the case of pathogenic bacteria, these functions include those central to their pathogenesis. Streptococcus pneumoniae is a major bacterial pathogen, causing a diverse range of diseases that account for significant morbidity and mortality worldwide. In this work, we characterize the polyamine biosynthetic pathway of S. pneumoniae, demonstrating that this organism produces spermidine from arginine. The synthesis of spermidine wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…The current annotation in TIGR4 is that of a LDC. The locus corresponding to SP_0916 in D39 is annotated to be an ADC, involved in spermidine synthesis (through indirect evidence), and is essential for the onset of autolysis (Potter and Paton, 2014). Pyridoxal-dependent decarboxylases in the polyamine biosynthesis pathways, such as SP_0916, belong to a family of enzymes with broad substrate specificity that can utilize arginine/lysine/ornithine.…”
Section: Introductionmentioning
confidence: 99%
“…The current annotation in TIGR4 is that of a LDC. The locus corresponding to SP_0916 in D39 is annotated to be an ADC, involved in spermidine synthesis (through indirect evidence), and is essential for the onset of autolysis (Potter and Paton, 2014). Pyridoxal-dependent decarboxylases in the polyamine biosynthesis pathways, such as SP_0916, belong to a family of enzymes with broad substrate specificity that can utilize arginine/lysine/ornithine.…”
Section: Introductionmentioning
confidence: 99%
“…PotD, is a potential next generation vaccine candidate and its efficacy increases in combination with several other pneumococcal protein candidates such as sortase A and glutamyl tRNA synthetase13192021. Recent studies showed delayed autolysis in a serotype 2 strain in which potD was deleted22. Although polyamines are implicated in a wide array of cellular processes, specific mechanistic roles for polyamines are yet to be assigned17.…”
mentioning
confidence: 99%
“…On the cell surface polyamines have been shown to influence biofilm formation in Bacillus subtilis and a number of Gram-negative pathogens. Spermidine biosynthesis exerts a regulatory influence on Streptococcus pneumoniae autolytic activity, possibly through cell wall structural interactions [ 93 , 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polyamine functions are generally poorly understood [ 94 ]. A complication to the assessment of this study’s polyamine data is the unique hypersensitivity of S. aureus to these molecules.…”
Section: Discussionmentioning
confidence: 99%